Higher dietary polyphenol intake is associated with reduced pain sensitivity and migraine-related disability: A cross-sectional analysis - Gabriele Bertotti; Alberto Roldán-Ruiz; Jaime Rodríguez-Vico; Andrea Gómez-García; Paula Marrero-Fernández; Miguel López-Moreno (PLoS ONE, 2026)
Introduction Migraine is a highly disabling neurological disorder characterized by recurrent headache attacks and altered pain processing. Emerging evidence suggests that dietary patterns rich in antioxidant compounds may modulate migraine-related pathophysiology, yet the specific association between polyphenol intake and objective pain sensitivity measures remains unclear. This study aimed to examine the association of dietary polyphenol with pain sensitivity and migraine-related disability in individuals with migraine. Materials and methods This cross-sectional study including 72 adults (65 women) with a confirmed migraine diagnosis according to ICHD-III criteria. Participants completed a 3-day dietary record, and polyphenol intake was estimated using the Phenol-Explorer database. Clinical outcomes included pressure pain thresholds (PPTs) at trigeminal and extratrigeminal sites, migraine-related disability (MIDAS), perceived stress (PSS), and handgrip strength. Associations were analyzed using Pearson correlations and multiple linear regression models adjusted for age, sex, BMI, energy intake, and comorbidities. Results Participants with longer disease duration reported higher polyphenol intake (p < 0.05). Total polyphenol intake was positively correlated with PPTs at the masseter (r = 0.27) and middle temporalis (r = 0.31), and inversely correlated with MIDAS scores (r = −0.25, all p < 0.05). In adjusted regression analyses, higher polyphenol intake predicted increased PPTs (masseter: β = 0.33; middle temporalis: β = 0.38) and lower MIDAS scores (β = −0.25, all p < 0.01). No associations were observed with handgrip strength or perceived stress. Conclusions Higher dietary polyphenol intake was associated with reduced pain sensitivity and lower migraine-related disability, suggesting a potential role for polyphenol-rich diets in migraine management. Further randomized controlled trials are needed to confirm these associations and explore the mechanisms through which polyphenol-rich diets may influence migraine-related outcomes.